Exploring Translation Strategies of Thesis Abstract Written by Non-English Department Students in The University of Mataram - Zahara, Intan Hardiani; Baharuddin, Baharuddin; Wardana, Lalu Ali; Putera, Lalu Jaswadi (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study investigates the translation problems, strategies, and the most frequently used strategy in translating Indonesian thesis abstracts into English. The subjects of this research comprised eight thesis abstracts written by non-English department students at the University of Mataram during the 2023 academic year. Utilizing Baker’s theory on translation problems and strategies, which encompasses eleven aspects, this study employed a mixed-methods approach, combining quantitative and qualitative analyses. The findings reveal a total of 78 translation problems across the eight Indonesian thesis abstracts. Among Baker's identified problems, only eight were observed, including: culture-specific concepts (31 instances), source language concepts not lexicalized in the target language (4 instances), semantically complex source language words (14 instances), a lack of specific terms in the target language (1 instance), differences in expressive meaning (8 instances), differences in form (2 instances), differences in frequency and purpose of specific forms (6 instances), and the use of loan words in the source text (12 instances). To address these challenges, seven out of eight translation strategies from Baker’s theory were employed in the English thesis abstracts. The most utilized strategy was translation using loan words (35 instances, 45%), followed by translation using a more general word (12 instances, 16%), translation using a neutral word (10 instances, 13%), translation by omission (10 instances, 13%), translation by paraphrase using a related word (4 instances, 5%), and the least employed strategies were translation using cultural substitution (3 instances, 4%) and paraphrase using unrelated words (3 instances, 4%). Of the 78 translation problems identified, 77 were resolved using the seven strategies, while one problem remained unsolved due to an unacceptable translation. This thesis aims to serve as a valuable reference for translators, English department students, and researchers in the field of translation. The findings indicate a significant need for enhanced support and resources in the translation process for non-English department students at the University of Mataram.